2016
DOI: 10.1186/s40064-016-3730-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of WeChat on sleep quality among undergraduates in Chongqing, China: a cross-sectional study

Abstract: BackgroundPrevious studies showed that social media is associated with sleep quality. WeChat (a native social media in China) is very popular in China, especially among the youth. In the second quarter of 2016, Tencent’s WeChat had 806 million monthly active users. The study sought to identify the influence of WeChat on the sleep quality among undergraduate students.MethodsA cross-sectional survey adopted a multi-stage stratified sampling survey to investigate undergraduates in Chongqing, China. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 41 publications
0
39
0
1
Order By: Relevance
“…The prevalences of sleep disturbances in the past 1–2 weeks, past month and past year were 15.7, 23.9 and 1.9%, respectively. Only one study reported sleep disturbance in the past year (Xu et al ., ). There was a significant difference in prevalence of sleep disturbances between studies using different PSQI cut‐off values ( Q = 49.6, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalences of sleep disturbances in the past 1–2 weeks, past month and past year were 15.7, 23.9 and 1.9%, respectively. Only one study reported sleep disturbance in the past year (Xu et al ., ). There was a significant difference in prevalence of sleep disturbances between studies using different PSQI cut‐off values ( Q = 49.6, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there have been a growing number of studies showing that smartphone use disorder/smartphone addiction (SA) 1 might be associated with poorer sleep quality, because these users stick around their smartphones too long, also in the evening or at night (Van den Bulck, 2003; Demirci et al, 2015). Interestingly, a new study by Xu et al (2016) observed that WeChat users have better sleep quality compared with non-users. The authors explained the initial contradictory findings in the context of stress relieving properties of WeChat [see also above the work by Mao (2014)].…”
Section: Overview On Previous Empirical Work: Motivations That Drivementioning
confidence: 99%
“…Up to now, studies that directly examined the relationship between SM use and sleep have yielded mixed results (e.g., Garett, Liu, & Young, 2016;Levenson, Shensa, Sidani, Colditz, & Primack, 2016;Xu et al, 2016). Whereas one study showed that SM frequency was related to more sleep disturbances, including more difficulty falling asleep and lower sleep quality (Levenson et al, 2016), other studies showed limited or no support for a negative relationship between SM use and sleep (Garett et al, 2016;Tavernier & Willoughby, 2014;Xu et al, 2016).…”
mentioning
confidence: 97%
“…Whereas one study showed that SM frequency was related to more sleep disturbances, including more difficulty falling asleep and lower sleep quality (Levenson et al, 2016), other studies showed limited or no support for a negative relationship between SM use and sleep (Garett et al, 2016;Tavernier & Willoughby, 2014;Xu et al, 2016).…”
mentioning
confidence: 99%